The importance of back contact modification in Cu2ZnSnSe4 solar cells: The role of a thin MoO2 layer. (August 2016) - Lopez-Marino, S.; Espíndola-Rodríguez, M.; Sánchez, Y.; Alcobé, X.; Oliva, F.; Xie, H.; Neuschitzer, M.; Giraldo, S.; Placidi, M.; Caballero, R.; Izquierdo-Roca, V.; Pérez-Rodríguez, A.; et al.
Abstract: Cu2 ZnSn(Sx Se1−x )4 (CZTSSe) photovoltaic absorbers could be the earth-abundant and low toxicity replacement for the already commercialized CuIn1−x Gax Se2 (CIGS) thin film technology. In order to make this possible, specific research efforts applied to the bulk, front and back interfaces must be performed with the aim of improving CZTSSe performance. In this paper the importance of back contact modification to obtain high efficiency Cu2 ZnSnSe4 (CZTSe) solar cells and to increase a paramount and limiting parameter such as VOC is highlighted. Several Mo configurations (monolayer, bi-layer and tri-layer) with different electrical and morphological properties are investigated in CZTSe solar cells. An optimum tri-layer configuration in order to minimize overselenization of the back contact during thermal annealing while keeping reasonable electrical features is defined. Additionally, a thin intermediate MoO2 layer that results in a very effective barrier against selenization and innovative way to efficiently assist in the CZTSe absorber sintering is introduced. The use of this layer enhances grain growth and subsequently the efficiency of solar cells increases via major VOC and FF improvement. An efficiency increase from 7.2% to 9.5% is obtained using a Mo tri-layer with a 20 nm intermediate MoO2 layer. Graphical abstract: Highlights: Several Mo configurations (mono-, bi- and tri- layers) tested in CZTSe solar cells. Mo tri-layer avoids overselenization and effectively controls MoSe2 thickness. Thin MoO2 prevents overselenization, increases CZTSe grain size and solar cell efficiency. Efficiency improvement from 7.2% to 9.5% with large enhancement of VOC, FF and RSH . One of the highest VOC for CZTSe technology 459 mV is obtained using 20 nm of MoO2 .